2020
DOI: 10.3390/su12051801
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Approach to Address Road Traffic Crashes beyond Cities: Hot Zone Identification and Countermeasures in Indonesia

Abstract: Addressing fatalities on road is a major concern in most countries in the world. South-East Asian countries are no exception. In Indonesia, three persons die on road every hour. Understanding where and how road traffic crashes happen is imperative before the most efficient countermeasures can be devised and implemented. In this paper, three tools-hot spots, hot zones and hot clusters-are used to identify sections of two main highways in the Province of Aceh that require most urgent action. Many countermeasures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was reported that full-face helmets can decrease facial injuries (Pruthi et al, 2010). The results showed that as compared with rural highways, the urban highways have more crash rates and a larger number of hot zones (Satria et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that full-face helmets can decrease facial injuries (Pruthi et al, 2010). The results showed that as compared with rural highways, the urban highways have more crash rates and a larger number of hot zones (Satria et al, 2020).…”
Section: Introductionmentioning
confidence: 96%